Fibrinolytic Activity of Thrombin Preparations - Brakman, Pieter; Klug, Panpit; Astrup, Tage (Thrombosis and Haemostasis, 1964)
Some thrombin samples have a slight unspecific protease activity probably caused by contaminating plasmin. All investigated samples were fibrinolytically active. This activity was caused by an activator of plasminogen. Fibrinolytic activity was apparently produced by two components of the thrombin preparations. One of these components was a contaminant with fibrinolytic activity but with no thrombin activity. This component could be separated from the thrombin by simple chemical procedures. The other fibrinolytic component appeared to be the thrombin molecule per se. It was not fibrinolytically active when used in the low concentrations required for clotting of fibrinogen, but in high concentrations, assayed on the fibrin plate, it activated plasminogen. In the accurate assay of fibrinolytic agents it is necessary to use preparations of thrombin from which the contaminating fibrinolytic agent has been removed.